2014
DOI: 10.1891/1933-3196.8.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the EMDR Protocol for Recent Traumatic Events on Acute Stress Disorder: A Case Series

Abstract: The purpose of this study was to evaluate the effectiveness of the eye movement desensitization and reprocessing (EMDR) protocol for recent traumatic events in the treatment of acute stress disorder. Within weeks of being exposed to an isolated traumatic event, 7 adults diagnosed with acute stress disorder were provided with multiple sessions of the EMDR protocol for recent traumatic events, an extended version of the EMDR therapy standard protocol. In each case, an individual’s subjective distress caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Such clients may benefit from interventions provided during the peritraumatic phase to help them process the trauma and overcome the harmful effects of PD. Interventions like prolonged exposure therapy (Leaman et al, 2013 ) and Eye Movement Desensitization and Reprocessing (EMDR; Buydens et al, 2014 ) have previously proven successful. At the same time, however, our findings indicated that it is initial avoidance symptoms, rather than appraisals of threat or PD, that predict future PTSD avoidance symptoms, and therefore it is these that should be targeted via evidence-based interventions provided during the peritraumatic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Such clients may benefit from interventions provided during the peritraumatic phase to help them process the trauma and overcome the harmful effects of PD. Interventions like prolonged exposure therapy (Leaman et al, 2013 ) and Eye Movement Desensitization and Reprocessing (EMDR; Buydens et al, 2014 ) have previously proven successful. At the same time, however, our findings indicated that it is initial avoidance symptoms, rather than appraisals of threat or PD, that predict future PTSD avoidance symptoms, and therefore it is these that should be targeted via evidence-based interventions provided during the peritraumatic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Terapia odwrażliwiania i przetwarzania za pomocą ruchu gałek ocznych (EMDR) Jest to ustrukturyzowana, indywidualna forma terapii obejmująca zazwyczaj od sześciu do dwunastu sesji -mogą się one odbywać raz albo dwa razy w tygodniu, także w kolejne dni. W ramach terapii pacjent przywołuje z pamięci traumatyczne doświadczenie, jednocześnie doświadczając bilateralnej stymulacji spowodowanej ruchem gałek ocznych, co zmniejsza intensywność i wyrazistość emocji związanych z traumą [44][45][46].…”
Section: Krótka Psychoterapia Eklektyczna (Bep)unclassified
“…Another study evaluated the effectiveness of this technique in people who recently experienced stressful situations. Their results showed the effectiveness of EMDR techniques and the prevention of subsequent stresses in such patients 15…”
Section: Introductionmentioning
confidence: 95%